2013
DOI: 10.3758/s13423-013-0393-4
|View full text |Cite
|
Sign up to set email alerts
|

Fragile visual short-term memory is an object-based and location-specific store

Abstract: Fragile visual short-term memory (FM) is a recently discovered form of visual short-term memory. Evidence suggests that it provides rich and high-capacity storage, like iconic memory, yet it exists, without interference, almost as long as visual working memory. In the present study, we sought to unveil the functional underpinnings of this memory storage. We found that FM is only completely erased when the new visual scene appears at the same location and consists of the same objects as the to-be-recalled infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 23 publications
5
99
0
1
Order By: Relevance
“…4 Some studies have also assessed how long it takes to achieve a stable retro-cue benefit by varying the stimulus onset asynchrony (SOA) between the offset of the retro-cue and presentation of a visual mask (Pinto, Sligte, Shapiro, & Lamme, 2013;van Moorselaar, Gunseli, et al, 2015). The visual mask diminished the retrocue benefit with SOAs up to 300 ms, further supporting this interval as the time needed to observe the full retro-cue benefit.…”
Section: Time Coursementioning
confidence: 99%
See 3 more Smart Citations
“…4 Some studies have also assessed how long it takes to achieve a stable retro-cue benefit by varying the stimulus onset asynchrony (SOA) between the offset of the retro-cue and presentation of a visual mask (Pinto, Sligte, Shapiro, & Lamme, 2013;van Moorselaar, Gunseli, et al, 2015). The visual mask diminished the retrocue benefit with SOAs up to 300 ms, further supporting this interval as the time needed to observe the full retro-cue benefit.…”
Section: Time Coursementioning
confidence: 99%
“…The evidence for this strong prediction is currently mixed. Sligte et al (2008) and Pinto et al (2013) observed that presenting a visual mask consisting of similar items in the same location as the memoranda prior to onset of the retro-cue abolished the retro-cue benefit. In contrast, Makovski (2012) observed retro-cue benefits even when a visual mask (multicolored dots presented at the same location as the color memoranda) was displayed prior to the retro-cue.…”
Section: Fragile/robust Wm Storesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of subsequent stimulation, the rich information in iconic memory transfers to a fragile but rich form of longer lasting (seconds) memory from which attention can select a number of objects and features that far surpasses the classic capacity of working memory (Landman, Spekreijse, & Lamme, 2003;Sligte, Scholte, & Lamme, 2008;Sligte, Wokke, Tesselaar, Scholte, & Lamme, 2010;Vandenbroucke, Sligte, & Lamme, 2011). This fragile shortterm memory is however erased by new visual stimulation (Pinto, Sligte, Shapiro, & Lamme, 2013;Sligte, Scholte, & Lamme, 2009), leaving an observer with only the content of working memory from which to report. The attention-gated promotion of elements of a weak but rich visual representation to cognitive report systems strongly resembles the theoretical construct of the attention-gated transition from phenomenal to access consciousness making these memory paradigms an interesting approach to sample the mechanisms of visual consciousness (Crick & Koch, 1990;Kouider, de Gardelle, Sackur, & Dupoux, 2010;Lamme, 2010).…”
Section: Memory Paradigmsmentioning
confidence: 99%